Purely co-Hopfian Modules - Z. T. Salman (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
Let R be an associative ring with identity and M a non â€“ zero unitary R-module.In this paper we introduce the definition of purely co-Hopfian module, where an R-module M is said to be purely co-Hopfian if for any monomorphism f Ë› End (M), Imf is pure in M and we give  some properties of this kind of modules.